2014
DOI: 10.1002/smll.201400642
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 3D Polymer Brushes by Dip‐Pen Nanodisplacement Lithography: Understanding the Molecular Displacement for Ultrafine and High‐Speed Patterning

Abstract: Dip-pen nanodisplacement lithography (DNL) is a versatile scanning probe-based technique that can be employed for fabricating ultrafine 3D polymer brushes under ambient conditions. Many fundamental studies and applications require the large-area fabrication of 3D structures. However, the fabrication throughput and uniformity are still far from satisfactory. In this work, the molecular displacement mechanism of DNL is elucidated by systematically investigating the synergistic effect of z extension and contact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
(42 reference statements)
2
13
0
Order By: Relevance
“…As shown in Figure , the axial ratio (the ratio between the length and the width of the nanodot) of the polymer and corresponding Au structures increased significantly with increasing z . The trend is attributed to the tip sliding along the y ‐axis due to cantilever deformation at high z , consistent with our recent study on the mechanism of DNL . When the dwell time is increased from 1 to 1000 ms, the resulting PMMA brush resist and Au nanostructures do not increase significantly in size.…”
Section: Photovoltaic Parameters Of the Fabricated Oscs Based On Varisupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure , the axial ratio (the ratio between the length and the width of the nanodot) of the polymer and corresponding Au structures increased significantly with increasing z . The trend is attributed to the tip sliding along the y ‐axis due to cantilever deformation at high z , consistent with our recent study on the mechanism of DNL . When the dwell time is increased from 1 to 1000 ms, the resulting PMMA brush resist and Au nanostructures do not increase significantly in size.…”
Section: Photovoltaic Parameters Of the Fabricated Oscs Based On Varisupporting
confidence: 90%
“…Because the lateral diffusion of initiator molecules is prohibited by the neighboring protecting SAM molecules after displacement, polymer chains grown from the initiated areas exhibit remarkable uniformity at the nanoscale as compared to when other SPL techniques are used to prepare such structures. Through precise control of the feature density and pattern design, DNL has shown promise for making complex 2D and 3D patterned nanostructures . More importantly, DNL is remarkably scalable by using an array of scanning tips .…”
Section: Photovoltaic Parameters Of the Fabricated Oscs Based On Varimentioning
confidence: 99%
“…Because the preassembled SAM significantly limits the lateral diffusion of the initiator ink, DNL ensures that the feature resolution is largely determined by the radius curvature of the AFM tip. In addition, the grafting density of the displaced initiators can be adjusted by the lithography force, which is a major difference from the ink transportation in classical DPN …”
Section: Development Of Dpn and Its Derivativesmentioning
confidence: 99%
“…Because the hardness of the silicon tip is larger than Au, when the applied force exceeded a certain value, the AFM probe was found to pierce into the Au film. It should be noted that, due to the slippage of the AFM tip under a large force, [40] each nanopit exhibited a boat-like shape rather than a perfect circle ( Figure S2, Supporting Information). It was found that any force below 10 µN did not provide obvious nanostructures.…”
Section: Scanning Probesmentioning
confidence: 99%